The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/sia.5114
|View full text |Cite
|
Sign up to set email alerts
|

Composition of uranium oxide particles related to TOF‐SIMS ion distributions

Abstract: Uranium oxide particles tens of micrometers in size, including natural and depleted UO 2 , U 3 O 8 , and UO 3 were analyzed using an IONTOF V time-of-flight secondary ion mass spectrometry (TOF-SIMS) V. Particulate samples were mounted on gold substrates made using a novel technique that reduced hydrocarbon contamination and volatile outgassing as well as provided an internal standard of Au x ion peaks to calibrate high masses. For UO 2 surfaces, the dominant U 3 O x and U 4 O y cations were U 3 O 6 + and U 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The environmental protection strategies for monitoring the migration processes of radionuclides in the geosphere and long storage of nuclear waste have involved complex models of environmental processes and experimental chemical, geochemical, physical and biological factors (Stoliker et al 2011;Ilton et al 2012;Jung et al 2012;Malaviya and Singh 2012;Chandrasekaran et al 2011;Sundararajan et al 2011;Mayer et al 2013;Walton and Mitchell 2013;Qiu and Burns 2013;Hocking et al 2013;Knope and Soderholm 2013). This complexity of the theoretical modeling and the experimental design of radionuclide migration in surface and groundwater; its speciation in wastewater, sorption onto soils, sediments and manure has been further complicated by the dual physical nature uranium between rare element and semiconductor as a result of the characteristics of 5f-electrons at an intermediate localization regime.…”
Section: Introductionmentioning
confidence: 99%
“…The environmental protection strategies for monitoring the migration processes of radionuclides in the geosphere and long storage of nuclear waste have involved complex models of environmental processes and experimental chemical, geochemical, physical and biological factors (Stoliker et al 2011;Ilton et al 2012;Jung et al 2012;Malaviya and Singh 2012;Chandrasekaran et al 2011;Sundararajan et al 2011;Mayer et al 2013;Walton and Mitchell 2013;Qiu and Burns 2013;Hocking et al 2013;Knope and Soderholm 2013). This complexity of the theoretical modeling and the experimental design of radionuclide migration in surface and groundwater; its speciation in wastewater, sorption onto soils, sediments and manure has been further complicated by the dual physical nature uranium between rare element and semiconductor as a result of the characteristics of 5f-electrons at an intermediate localization regime.…”
Section: Introductionmentioning
confidence: 99%
“…The use of LA-ICP-MS for this purpose has been discussed briefly, but secondary ion mass spectrometry (SIMS) is currently the most common technique for spatially resolved MS . SIMS enables concurrent determination of the shape, composition, and isotopic ratios present in a sample, indicating the homogeneity of a sample at relatively small scales (generally on the order of micrometers). , Ionization is achieved by focusing an ion beam onto the sample, causing secondary ions to be ejected. Since the sample is only ionized at its surface, minimal sample preparation is required for SIMS and imaging is also possible.…”
Section: Microanalytical Techniquesmentioning
confidence: 99%
“…The authors concluded that this enhanced method will be a valuable tool to assist in the certication of future RMs. It was possible 49 to distinguish between different valences states such as UO 2 , U 3 O 8 and UO 3 on surface layers and through depth proles of U-oxide particles by interrogating the ion distributions measured by TOF-SIMS.…”
Section: Instrumental Analysismentioning
confidence: 99%